Adequacy of Coverage, Targeting and Benefits of Social Protection Programs - Sabbih, Mostafa Amir; Coudouel, Aline (World Bank, Washington, DC, 2021)
In Bangladesh, regular increases in social protection budget have typically prioritized increases in coverage over increases in benefit size or amounts. To maximize the impact of social protection (SP) programs, it is critical to: (1) align the allocation of resources with national policies and strategies; (2) design programs that are able to reach their intended beneficiaries with adequate coverage and level of benefits; (3) ensure efficiency in programming and financing; and (4) ensure efficiency in the actual delivery of programs at the local level. This policy note analyses point (2), the adequacy of SP programs in Bangladesh, and highlights areas where challenges remain and proposes policy reforms to address those. It focuses on the three elements of the design of social protection (SP) programs that are critical to maximum impacts on poverty and vulnerability: (1) the extent to which programs have the right size and coverage; (2) the extent to which programs effectively reach or target the right beneficiaries; and (3) the extent to which programs provide these beneficiaries with the right benefits. The optimal combination of these elements depends on programs’ policy objectives, the needs or demands of target population groups, the types of beneficiaries or programs, and available resources.